Tweezer-Assisted Subwavelength Positioning of Atomic Arrays in an Optical Cavity - M. Seubert; L. Hartung; S. Welte; G. Rempe; E. Distante (PRX Quantum)
We present an experimental technique that enables the preparation of defect-free arrays of ^{87}Rb atoms within a microscopic high-finesse optical standing-wave cavity. By employing optical tweezers, we demonstrate atom positioning with a precision well below the cavity wavelength, a crucial requirement for cavity-QED experiments in which maximum atom-cavity coupling strength is required. We leverage our control capabilities to assemble an array of up to seven atoms with an efficiency that exceeds previous probabilistic methods by 4 orders of magnitude. The atoms are subsequently transferred from the tweezer array to a two-dimensional intracavity optical lattice that offers enhanced coherence for spin qubits while maintaining strong atom confinement. Our system overcomes the efficiency limitations of previous probabilistic loading techniques of cavity-coupled atom arrays and opens the path to multiqubit quantum networks with atoms strongly coupled to optical cavities.